2015
DOI: 10.1002/cbm.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of work skills programmes for offenders with mental disorders: A systematic review

Abstract: There is modest evidence to support inclusion of specific work skills programmes in the treatment of offenders with mental disorder. Future studies should be of theoretically driven programmes, such as Individual Placement Support (IPS), and use a standard set of relevant outcome measures and long enough follow-up for testing the effectiveness of any programme on engagement in competitive, paid employment as, even if skilled, offenders with mental disorder must constitute a hard to place group. Copyright © 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Commitment to treatment measures may be promoted by recovery- and strength-based practices, including peer support ( 56 , 57 ), opportunities for meaningful occupation ( 58 ), and work skills programs, such as Individual Placement Support (IPS) ( 59 ). Accordingly, Livingstone ( 60 ) concluded that success in the forensic mental health system is seen as a dynamic, collaborative process rather than an end state.…”
Section: Discussionmentioning
confidence: 99%
“…Commitment to treatment measures may be promoted by recovery- and strength-based practices, including peer support ( 56 , 57 ), opportunities for meaningful occupation ( 58 ), and work skills programs, such as Individual Placement Support (IPS) ( 59 ). Accordingly, Livingstone ( 60 ) concluded that success in the forensic mental health system is seen as a dynamic, collaborative process rather than an end state.…”
Section: Discussionmentioning
confidence: 99%
“…We thus labeled Class 3 Extensive Criminogenic Needs and Class 4 Acute and Extensive Criminogenic Needs, as individuals of the latter group did not significantly differ from the former on any characteristics, but showed a greater level of need, as per their much higher rates of charges relating to acquisitive crimes. In addition to interventions that address antisociality and other criminogenic needs, individuals with Acute and Extensive Criminogenic Needs may benefit from initiatives aimed at increasing resources, such as Housing First and supported employment (Talbot et al, 2017; Woodhall-Melnik & Dunn, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent review of the literature on employment of ex-prisoners with severe mental illness documented a specific lack of employment opportunities for these individuals (25) who encounter a myriad of barriers to employment including stigma, social isolation, substance misuse, and low educational attainment (26). Furthermore, Talbot and colleagues (27) reviewed the evidence base for work skills program for offenders with mental disorders, and reported that while a range of employment program have been developed for these individuals, the evidence base for their effectiveness is limited in terms of impact on mental health, substance misuse, or reoffending rates.…”
Section: Employment Supportmentioning
confidence: 99%